IMPLEMENTASI MODEL FUZZY SAW DALAM PENILAIAN KINERJA PENYULUH AGAMA (Studi Kasus: Kementerian Agama Kabupaten Pringsewu) - Muhamad Muslihudin; Didik Kurniawan; Ika Widyaningrum (Jurnal TAM (Technology Acceptance Model), 2017)
Purpose in this study is to find and accused of performance employees the ministry of religion in counseling religion in kabupaten pringsewu and whatever that becomes obstacle barrier performance employees the ministry of religion in counseling held in kabupaten Pringsewu. Of research in the ministry of religious affairs distric pringsewu. Data collection collected by interviews and documentation. Analysis the data used was data analysis qualitative in starting by making data collection, reduction data, and presentation of data and the withdrawal of conclusion. This research using a technique collection, research room namely by data collection through the activities of observation, research, interview documentation to get data clearer in accordance with required in research. In the results of research obtained conclusion on performance counselors religion the ministry of religion in counseling religion in kabupaten pringsewu.The guidance had run quite well where stage the training is do three stages covering guidance, counseling, and lighting. Performance evaluation of among others for the delivery of material, discipline, responsibility, absentee, cooperation. From the study obtained the result that father m.Including extension workers miftahudin religion with the best grades namely 0.91.